First-principles calculations study the mechanical and thermal properties of Cr–Al–B ternary borides. (March 2021) - Wei, Jiang; Zhang, Lei; Liu, Yangzhen
Abstract: Cr–Al–B ternary borides are considered as promising materials to apply in high temperature environment due to their outstanding thermal properties. However, the detail mechanical properties of these borides are still not very clear. To better exploit the potential ability of these borides, some basic physical-chemical properties such as structure stability, stiffness, hardness especially for anisotropic elasticity and sound velocity are studied by first-principles calculations. The results showed that there are four compounds, namely CrAlB, Cr2 AlB2, Cr3 AlB4 and Cr4 AlB6, have a stable crystal structure. The Cr4 AlB6 is the most in-compressible and stiff boride and the Cr2 AlB2 is the most brittle boride among the Cr–Al–B TMBs. In addition, the strongest shear anisotropic degree of the CrAlB is along (100) crystal plane while the Cr3 AlB4, Cr4 AlB6 and Cr2 AlB2 are along (010) crystal plane. The bulk moduli profile of the Cr–Al–B TMBs are almost spherical, especially observed in projection of (001), (010) and (100) planes which indicate that the bulk modulus is weak anisotropy. The Cr4 AlB6 has a larger Debye temperature than the other borides. This work will provide some helpful statistics for further investigating Cr–Al–B ternary borides with outstanding mechanical and thermal properties. Highlights: The physical-chemical properties of Cr–Al–B ternary borides are systematically studied. The Cr4 AlB6 is the most in-compressible and stiff boride. The anisotropic degree of CrAlB is stronger than other compounds.